Pemberdayaan Orang Tua Pasien melalui Edukasi Gizi dan Kesehatan dalam Pencegahan Stunting di Poliklinik Anak RSUD Kota Kendari - Hilda Harun; Paridah; Fifi Nirmala; Jusniar Rusli Afa; Rastika Dwiyanti Liaran (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Stunting remains a major public health concern in Indonesia, as it can severely affect children’s physical growth and cognitive development over the long term. Preventive efforts at the household level require improvements in parents’ knowledge and behaviors through targeted health education. This community service program aims to strengthen the role of parents of young children through nutrition and health education as a strategy to prevent stunting at the Pediatric Polyclinic of Kendari City General Hospital. The program was implemented through individual health counseling using an Interpersonal Communication (IPC) approach, supported by educational leaflets as complementary media. The primary targets of this activity were parents or primary caregivers of toddlers visiting the clinic.The activity demonstrated positive responses with active participant engagement, strong support from healthcare workers, and high levels of enthusiasm for the information delivered. This indicates a considerable need for practical knowledge on appropriate nutrition and child care within families. Among the 20 participants, 15 attended the full counseling session and reported that the materials provided were beneficial for application at home. These findings emphasize that health education integrated into healthcare services can serve as an effective strategy to improve family nutrition literacy and accelerate stunting reduction efforts. Continuous educational activities are required to ensure that behavioral changes are sustained and optimized as part of stunting prevention initiatives in Kendari City